Exploring the Transactional Communication Model in Managing Work Responsibilities - Amin, Fatimah Hidayahni; Mohamad, Andi Riswan; Sudding, Muhammad Fahri Jaya; Susanto, Ashabul Kahfi; Hanafie, Nurharsya Khaer (Celebes Journal of Language Studies, 2025)
This study aims to identify and determine the transactional communication model using Shockley-Zalabak’s Organizational Communication Process Model used by the employees in delivering transactional utterances in workplace management. The research method was qualitative with a descriptive design. The subjects of this study are employees in the academic and broadcasting workplaces. Data on the transactional communication model were collected through transcripts of observations accompanied by audio recordings. The findings of the study reveal that communication within organizational settings is fundamentally transactional, interactive, and context-dependent. Across all extracts, communication emerges not as a simple transmission of information but as a co-created process shaped by hierarchical roles, organizational procedures, feedback loops, and interpersonal dynamics.